The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1073/pnas.1714249114
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of N- and O-glycans in cellulase activity and stability

Abstract: In nature, many microbes secrete mixtures of glycoside hydrolases, oxidoreductases, and accessory enzymes to deconstruct polysaccharides and lignin in plants. These enzymes are often decorated with N- and O-glycosylation, the roles of which have been broadly attributed to protection from proteolysis, as the extracellular milieu is an aggressive environment. Glycosylation has been shown to sometimes affect activity, but these effects are not fully understood. Here, we examine N- and O-glycosylation on a model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 43 publications
5
101
1
3
Order By: Relevance
“…Another issue concerns the effect of glycosylation on linker structure and dynamics. Such glycosylation is known to happen in CAZymes from fungi (39,45) and actinomycetes (46), and its impact is currently receiving considerable attention (39,45). In their study on the C. fimi xylanase, Poon et al (43) concluded that glycosylation of the 20-residue Pro-Thr linker had limited effects on linker structure and dynamics.…”
Section: Cellulose Oxidation By a Modular Lpmomentioning
confidence: 99%
See 1 more Smart Citation
“…Another issue concerns the effect of glycosylation on linker structure and dynamics. Such glycosylation is known to happen in CAZymes from fungi (39,45) and actinomycetes (46), and its impact is currently receiving considerable attention (39,45). In their study on the C. fimi xylanase, Poon et al (43) concluded that glycosylation of the 20-residue Pro-Thr linker had limited effects on linker structure and dynamics.…”
Section: Cellulose Oxidation By a Modular Lpmomentioning
confidence: 99%
“…Studies on the roles of glycosylated linkers in fungal modular CAZymes have revealed an impact of glycosylation on substrate binding and proteolytic resistance, but information on the impact of glycosylation on linker shape and dynamics is scarce. Interestingly, in a recent study, Amore et al (45) concluded that glycosylation of the linker in a fungal cellobiohydrolase ensures the separation between the catalytic domain and the CBM. The present data show that the nonglycosylated linker of ScLPMO10C has an extended conformation that separates the domains.…”
Section: Cellulose Oxidation By a Modular Lpmomentioning
confidence: 99%
“…C) and in its close homolog Th Cel7B . Although it is widely acknowledged that a combination of several factors are responsible for stabilizing thermophilic structures , we note that the features listed above point as elements contributing to the high T m of Re Cel7B . In addition to this, the presence of N‐glycans is probably important for the very high solubility of Re Cel7B, another desirable trait from an industrial perspective .…”
Section: Discussionmentioning
confidence: 79%
“…Due to the complexity, recalcitrance and insolubility of the plant biomass [2], high enzyme titers must be used to ensure e cient biomass hydrolysis, and this challenges the economic feasibility of the process. To overcome this, extensive research has sought to either engineer catalytically more e cient enzymes or to develop more e cient expression hosts such as Trichoderma reesei [3], Saccharomyces cerevisiae [4] and Aspergillus niger [5]. The latter effort has enabled industrial production of cellulases, but usually with a range of isoforms with different apparent molecular weights [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the N-glycans on TrCel7A have been characterized as high-mannose type (Man), containing from Man 5-9 residues linked to a chitobiose core of two N-acetylglucosamine units (GlcNAc) 2 , whereas the O-glycans consist mainly of Man 1-4 randomly distributed in both the linker region and CBM domain with the majority bound to the linker of TrCel7A [7,10]. Recently, Amore et al (2017) [3] performed extensive mass spectrometry (MS) characterization of the different N-glycoforms of TrCel7A expressed in T. reesei, and this work indicated a broader complexity of N-glycans, including the presence of fucose, galactose or additional Nacetylglucosamine residues. The glycan complexity is not only in uenced by the expression hosts and their extracellular activities of glycosidases and transferases, but also the composition of the growth media [11].…”
Section: Introductionmentioning
confidence: 99%